Workplace Well-Being Through Nature-Based Solutions: A Fuzzy Framework for Decision-Making - Bressane, Adriano [UNESP]; de Castro, Marcos Vinícius [UNESP] (MDPI, 2025)
The rise in performance and health concerns presents a complex challenge to workplace well-being. While existing research highlights the positive impact of exposure to nature on well-being, there is a gap in supporting biophilic building designs in workplaces. This study addresses this issue by introducing a Type-1 Interval Fuzzy Set (IFS) framework to assess workplace health, and recommends Nature-Based Solutions (NbS) for enhancement. The proposed framework comprises two fuzzy subsystems targeting environmental comfort and occupational health that are integrated into a third subsystem to provide tailored NbS recommendations. A case study conducted in a coworking space validated the framework’s practical application, revealing significant improvements in environmental and occupational conditions. Key findings include a reduction in absenteeism, enhancement in employee satisfaction, and creation of more comfortable and restorative environments. Recommendations, such as green walls, indoor gardens, and natural light filters, have been shown to effectively mitigate discomfort and promote well-being. The framework demonstrated flexibility in managing uncertainties, optimizing resource allocation, and providing targeted interventions for workplace conditions. These results highlight the framework’s potential as a robust decision-support tool for improving workplace health and well-being through systematic and evidence-based strategies.
Keywords: artificial intelligence; environmental health; fuzzy logic; nature-based solutions; workplace well-being